Public employment in the Middle East and North Africa - Ragui Assaad; Ghada Barsoum (IZA World of Labor, 2019)
Public sector hiring has been an essential component of the social bargains that have maintained political stability in the Middle East and North Africa (MENA). As these bargains eroded, public sector workforces contracted in relative terms owing to a partial freeze on hiring and the promise of lifetime job security for incumbent workers. This had profound effects on the age composition of the workforce. The upcoming retirement of many workers provides an opportunity to restructure public sector hiring to emphasize meritocratic recruitment processes and performance-based compensation systems.
Keywords: J21; J45; J48; 330; MENA; Middle East and North Africa; gender; age structure; public sector